2022
DOI: 10.3390/e24101334
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Chip-Based Quantum Key Distribution

Abstract: Quantum key distribution (QKD), guaranteed by the principles of quantum mechanics, is one of the most promising solutions for the future of secure communication. Integrated quantum photonics provides a stable, compact, and robust platform for the implementation of complex photonic circuits amenable to mass manufacture, and also allows for the generation, detection, and processing of quantum states of light at a growing system’s scale, functionality, and complexity. Integrated quantum photonics provides a compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 201 publications
(211 reference statements)
0
10
0
Order By: Relevance
“…In 2012, the measurement-device-independent (MDI) QKD protocol was first proposed, offering practicality and immunity to attacks on all detectors [9]. In 2014, the round-robin differential phase shift (RRDPS) QKD protocol was introduced, and its security was demonstrated without relying on detecting channel disturbances [5,[11][12][13]21]. In 2015, Wang Xiangbin and colleagues from China proposed a measurement-device-independent QKD protocol based on four different intensities of decoy states [25].…”
Section: Quantum Key Distribution Technologymentioning
confidence: 99%
“…In 2012, the measurement-device-independent (MDI) QKD protocol was first proposed, offering practicality and immunity to attacks on all detectors [9]. In 2014, the round-robin differential phase shift (RRDPS) QKD protocol was introduced, and its security was demonstrated without relying on detecting channel disturbances [5,[11][12][13]21]. In 2015, Wang Xiangbin and colleagues from China proposed a measurement-device-independent QKD protocol based on four different intensities of decoy states [25].…”
Section: Quantum Key Distribution Technologymentioning
confidence: 99%
“…[94] have developed a low‐cost, short‐range QKD system for consumer applications that can support a peak SKR of 20 Kbps. With the recent advances in integrated photonics and chip‐based QKD [95], considerable progress has been made in the development of handheld QKD terminals [96] that can be used for short‐range applications including secure ATM transactions and device‐to‐device quantum key exchange [97]. Further advancement in chip‐based QKD technology would enable the widespread commercialisation of mobile QKD devices in future 6G networks.…”
Section: Quantum Information Technologies In 6g Networkmentioning
confidence: 99%
“…However, the practical MDI-QKD still experiences relatively low key rates compared to the conventional BB84 protocol due to the requirement of Bell-state measurements. Apart from these advances, adopting QKD widely has been a challenge, and it has been demonstrated that large-scale deployment will likely require chip-based devices for improved performance, miniaturization, and enhanced functionality 12 18 . Most significantly, these integrated photonic chips offer numerous benefits such as low cost, low power consumption, and well-established batch fabrication techniques 19 .…”
Section: Introductionmentioning
confidence: 99%